Energy efficiency of working vessels – A framework. (1st February 2017) - Lützen, Marie; Mikkelsen, Lars Lindegaard; Jensen, Signe; Rasmussen, Hanna Barbara
Abstract: For many years, there has been a growing focus on the energy efficient operation of vessels, and several performance systems are available on the market. However, most of these systems have been developed for long-distance sailing, and cannot be used directly on working vessels. The aim of the paper is to present a conceptual framework, which describes the overall decision structures in connection with energy efficient operations of working vessels. The framework consists of three models: the first model describes the operational modes and activity states of a vessel; the second model describes the conceptual dependency between the different actors in the operational context and the last model presents the conceptual solution model, which integrates the two other models. The models are developed based on nearly 50 interviews conducted with seafarers and office staff, procedure descriptions, and observations during fieldwork on board the ships. The proposed framework will form the basis for a future multi-layered decision support system.